"Palabras tendidas. La obra de Vittorio Bodini entre España e Italia" de Juan Carlos de Miguel y Canuto (ed.) - Miralles Guardiola, Almudena (Estudios Románicos, 2021)
The volume reviewed, Palabras tendidas. La obra de Vittorio Bodini entre España e Italia,, is born from the necessary and right intention to place the hispanist and poet in the place he deserves in the Spanish literary environment of our time, for his inestimable contribution to the dissemination of Spanish literature beyond our borders. The nine studies gathered analyze different facets in Bodini's literary work, and reveal the deep union of the Italian with Spain, which was decisive both in his life and in his work.